1999
DOI: 10.1074/jbc.274.42.30163
|View full text |Cite
|
Sign up to set email alerts
|

Increased Myosin Light Chain Phosphorylation Is Not Required for Growth Factor Stimulation of Collagen Matrix Contraction

Abstract: Previous research suggested the possibility that contraction of floating collagen matrices by human fibroblasts required increased myosin light chain (MLC) phosphorylation. In the current studies, we show that increased MLC phosphorylation was neither necessary for platelet-derived growth factor (PDGF)-dependent matrix contraction nor sufficient for lysophosphatidic acid (LPA)-dependent contraction. In contrast, increased MLC phosphorylation did appear to be coupled to the formation of stress fibers by cells s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…PDGF-dependent floating matrix contraction required myosin II judging from its sensitivity to inhibition by blebbistatin and the Rho kinase inhibitor. MLC kinase did not appear to be required, however, and no stimulation of MLC-diphosphorylation was detected, consistent with previous observations of PDGF-treated cells on planar surfaces (21,23). Because PDGF treatment of fibroblasts in collagen matrices activates Rac and not Rho (9), as has been shown for cells on planar surfaces (42,43), Rho activity necessary for PDGF-stimulated contraction likely is provided by a mechanism other than growth factor stimulation, e.g.…”
Section: Figsupporting
confidence: 77%
See 3 more Smart Citations
“…PDGF-dependent floating matrix contraction required myosin II judging from its sensitivity to inhibition by blebbistatin and the Rho kinase inhibitor. MLC kinase did not appear to be required, however, and no stimulation of MLC-diphosphorylation was detected, consistent with previous observations of PDGF-treated cells on planar surfaces (21,23). Because PDGF treatment of fibroblasts in collagen matrices activates Rac and not Rho (9), as has been shown for cells on planar surfaces (42,43), Rho activity necessary for PDGF-stimulated contraction likely is provided by a mechanism other than growth factor stimulation, e.g.…”
Section: Figsupporting
confidence: 77%
“…Previously, we showed by using the ureaglycerol method that LPA but not PDGF stimulated both monoand diphosphorylation of fibroblasts on collagen-coated coverslips, but for technical reasons the urea-glycerol method could not be used for fibroblasts in collagen matrices (23). Therefore, MLC phosphorylation in fibroblasts in collagen matrices was assessed using antibodies specific to (di)phosphorylated MLC with total MLC as a loading control.…”
Section: Fibroblast-collagen Matrix Remodelingmentioning
confidence: 99%
See 2 more Smart Citations
“…In nonmuscle cells, elevated cAMP has been shown to cause the following: 1) alterations in cell morphology; 2) inhibition of cell motility; 3) disruption of actin filaments; 4) pericyte relaxation in a silicone rubber wrinkling assay; and 5) fibroblast relaxation in a collagen gel assay (1,(25)(26)(27)(28)(29). In endothelial cells, preliminary studies have shown that elevations in cAMP correlate with an increase in MLCK phosphorylation (13,30) and a decrease in RLC phosphorylation.…”
mentioning
confidence: 99%